Merger waves and the Austrian business cycle theory (2013)
Following standard Austrian School theory, in this paper I identify merger waves as parts of Austrian type business cycles. As indicated by Mises, Rothbard and Hayek, when loan rates are reduced below their natural level through bank credit expansion this falsifies the monetary calculation of capitalist-entrepreneurs. As a result, new investments are initiated that calculation showed were not profitable before the interest rate reduction. On the other hand, the fall in interest rates falsifies households’ appraisals of their income and wealth, which turns them overly optimistic and causes them to over-consume, save less and go into debt. As a consequence of these developments the economy does not have enough resources for the completion of the new projects and businesses must increasingly withdraw the resources from other companies. I conclude that the increase in investment activity and the accompanying “resource crunch” cause a merger wave that helps prolong the boom phase of the cycle. The merger wave ends when the credit expansion is not sufficient to sustain the economic boom (which usually occurs when central banks finally let interest rates rise again and an overextended financial system tightens credit standards) and the bust phase begins. On the other hand, if the newly created fiduciary media does not enter the economy through the loan market to finance business investment, there should be no pronounced and sustained increase in merger activity followed by an economic bust.